Development of Animation Video Learning Media Based on Local Wisdom Tri Kaya Parisudha in Cultural Diversity Material Content Social Science Learning Grade IV Elementary School - Darma Putra, I Gusti Ngurah Agung; Sujana, I Wayan (Jurnal Ilmiah Sekolah Dasar, 2021)
This research is motivated by the problem of the less of innovative learning media and the application of conventional methods which have an impact on students' interest and understanding of social science subject matter. The purpose of this research is to develop an animation video based on local wisdom of Tri Kaya Parisudha on social sciences learning in grade IV Elementary School. This research is a development research using the ADDIE model which is carried out in grade IV SD No. 3 Abiansemal. The subjects of this research are one lecturer as a subject content expert, one lecturer as an expert in learning design, one lecturer as an expert in learning media, and 12 grade IV Elementary School students for individual trials and small group trials. The data collection method used is a non-test method using a questionnaire with the instrument used is a questionnaire. The data analysis technique used is descriptive quantitative analysis technique. Based on the results of data analysis, obtained results (1) the results of the validity test by the subject content expert obtained a score of 95.83% (very good), (2) the results of the validity test by the instructional design expert obtained a score of 85% (good qualification), (3) the results of the validity test by media experts obtained a score of 88.33% (good qualification), (4) the individual trial results obtained a score of 95.83% (very good qualification), and (5) the results of the small group trial obtained a score of 97, 50% (very good qualification). So, it can be concluded that the video animation media based on local wisdom of Tri Kaya Parisudha is feasible for use as a learning media for social sciences content in grade IV elementary school. The implication of this research is the video animation learning media based on Tri Kaya Parisudha's Local Wisdom can make students learn independently, so that the learning process becomes more interesting, effective, and has a positive effect on student learning outcomes.